Slope effect on dynamic p–y backbone curve in dry sand. Issue 144 (May 2021) - Tran, Nghiem Xuan; Nguyen, Bao Ngoc; Yoo, Byeong-Soo; Kim, Sung-Ryul
Abstract: This study aims to evaluate the slope effect on the dynamic p – y backbone curve, which is a worldwide simplified tool in the seismic design of pile foundations. Data of dynamic centrifuge tests on single and group piles in sloping sandy ground were adopted to derive soil resistance and pile displacement. Meanwhile, the free-field soil displacement was computed by performing three-dimensional numerical simulations of centrifuge models excluding the pile-supported structure. Dynamic p – y loops of soil resistance and pile displacement relative to the free-field soil displacement showed an irregular shape with the occurrence of large residual displacement. The soil resistance mobilized at the free-head pile was smaller than that at the fixed-head pile because of the difference in the phase responses. An empirical factor was introduced to account for the slope effect on the dynamic p – y backbone curve, which was formed by fitting peak points of the dynamic p – y loops with a hyperbolic function. Pseudo-static analyses applying the suggested dynamic p – y backbone curve showed good agreement with the centrifuge test data. Highlights: Slope effect on p – y curves was analyzed using centrifuge tests and numerical simulations. Different soil resistance was mobilized according to phase responses between pile and soil. Shape of dynamic p – y loop became irregular with residual displacement of slope. A proposed empirical factor accounting for slope effect on dynamic p – y backbone curve.